Nephrotic Syndrome Associated with Lung Cancer: A Rare Case of Malignancy Associated with AA Amyloidosis - Victor Gueutin; Anne-Lyse Langlois; Nathalie Shehwaro; Ryme Elharraqui; Philippe Rouvier; Hassane Izzedine (Case Reports in Nephrology)
Nonhematologic malignancies are rarely reported to be associated with AA amyloidosis. Although the association between renal cell carcinoma and systemic AA amyloidosis has been established, the evidence linking pulmonary cancer to AA amyloidosis is scarce. Here, a case of biopsy-proven renal AA amyloidosis complicated with nephrotic syndrome associated with lung carcinoma is reported.